Bankers Without Borders? : Implications of Ring-Fencing for European Cross-Border Banks - Makarova, Yuliya; Cerutti, Eugenio; Ilyina, Anna.; Schmieder, Christian (Washington, D.C. : International Monetary Fund, 2010)
This paper presents a stylized analysis of the effects of ring-fencing (i.e., different restrictions on cross-border transfers of excess profits and/or capital between a parent bank and its subsidiaries located in different jurisdictions) on cross-border banks. Using a sample of 25 large European banking groups with subsidiaries in Central, Eastern and Southern Europe (CESE), we analyze the impact of a CESE credit shock on the capital buffers needed by the sample banking groups under different forms of ring-fencing. Our simulations show that under stricter forms of ring-fencing, sample banking groups have substantially larger needs for capital buffers at the parent and/or subsidiary level than under less strict (or in the absence of any) ring-fencing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet